Sayyid Qutb’s Interpretation in Fi Zhilalil al-Qur’an of the Qur’anic Verses About Children and Their Revelance to The Childfree - Annisa Fadhilah; Sri Mulyati; Khairunnisa Khairunnisa; Rohma Nur Aisya; Anwar Sidik; Rizka Sari; Andri Syahputra (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2025)
This study therefore asks: How does the childfree phenomenon reflect a disorientation of the purposes marriage in Islam, and how can it be critically understood through Sayyid Qutb’s thematic interpretation of the Qur’an? This research employs a qualitative library research design with a thematic tafsir (tafsir maudhu‘i) approach based on Sayyid Qutb’s Fi Zhilalil Qur’an, while also incorporating perspectives from sociology, gender studies, and demographic theory to ensure a multidisciplinary foundation. The findings indicate that the childfree decision reflects complex socio-cultural dynamics shaped by economic pressures, gender equality discourse, and lifestyle individualism yet it stands in contrast to the Islamic worldview that regards children as an amanah (trust), a source of tranquility, and a continuation of civilization. This study contributes by contextualizing Sayyid Qutb’s tafsir in contemporary debates, demonstrating that rejecting children for purely worldly reasons signals a spiritual crisis and weakens collective responsibility. It further highlights the need for Qur’an-based premarital education in Indonesia to restore the balance between individual autonomy and socio-religious responsibility.